2015
DOI: 10.1016/j.mfglet.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of external cooling configuration on friction surfacing of AA6082 T6 over AA2024 T351

Abstract: Friction surfacing is a solid-state surface engineering technology. Previous studies have shown that underwater friction surfacing has some advantages in efficiency and homogeneity of the deposited material. To use these advantages a water spray cooling system was implemented to achieve a more flexible process. This concept has been investigated by depositing Al alloy AA6082 T6 on AA2024 T351 substrate. The efficiency of the process was increased from 19% to 31% without influencing the properties of the deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It is reported that the deposition efficiency is a function of energy input for a fixed volume and affects the deposited material. The deposition geometry is also reported as a function of the process parameters and temperature evolution during friction surfacing [109,110]. From the direction of friction surfacing, 6xxx series alloys as the tool material are more explored than 6xxx series alloys as the substrate material [109][110][111][112][113].…”
Section: Friction Surfacingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the deposition efficiency is a function of energy input for a fixed volume and affects the deposited material. The deposition geometry is also reported as a function of the process parameters and temperature evolution during friction surfacing [109,110]. From the direction of friction surfacing, 6xxx series alloys as the tool material are more explored than 6xxx series alloys as the substrate material [109][110][111][112][113].…”
Section: Friction Surfacingmentioning
confidence: 99%
“…The deposition geometry is also reported as a function of the process parameters and temperature evolution during friction surfacing [109,110]. From the direction of friction surfacing, 6xxx series alloys as the tool material are more explored than 6xxx series alloys as the substrate material [109][110][111][112][113]. In this review, the use of the 6xxx series as the substrate material is considered.…”
Section: Friction Surfacingmentioning
confidence: 99%
“…Fitseva et al [11] analyzed the deposition behavior and process characteristics of titanium alloys with various rotational speeds and found increasing the rotational speed causing an increase in the coating width and thickness and also increasing the deposition efficiency up to 39%. Krohn et al [12] investigated the influence of external cooling on friction surfaced between aluminium alloys and found the intensity and location of cooling affecting process characteristics and modifying the coating geometry. In their experimental work, Stegmueller et al [13] made a study of the inductive heating effect between stainless steel and aluminium substrate and found an increase in the rotational speed causing a decrease in the coating mass and thickness but an increase in flash masses of the consumable rod.…”
Section: Introductionmentioning
confidence: 99%
“…Both the material fraction going into the flash as well as the obtained coating geometry can vary. The most significant influencing factors are the materials used [2], the rotational and translational speed as well as axial force [3] and optional cooling measures [4]. FS is of interest a.o.…”
Section: Introductionmentioning
confidence: 99%